Role of Engaging Leadership in Work Engagement: Basic Psychological Needs Satisfaction as Mediator - rohinsa, meilani; Gunawan, Gianti; Puspitasari, Indah (Analitika: Jurnal Magister Psikologi UMA, 2024)
The most important asset of an organization is its human resources. A situation where employees have an emotional and intellectual commitment to the organization or have work engagement is a condition that is highly expected by all organizations. This research aims to examine the role of engaging leadership on work engagement, mediated by basic psychological needs. This research involved a total of 140 participants (men= 73; women= 67) who were private employees in the city of Bandung. The average age of male respondents was 36.8 years and female were 33.9 years. In this research, three measuring instruments were used, namely, the utrech work engagement scale, the basic psychological needs satisfaction scale, and the engaging leadership scale. The results of the mediation test showed that the mediation that occurred was partial. This means that engaging leadership shows its role in work engagement, with or without being mediated by the fulfillment of basic psychological needs. These findings provide a scientific contribution to the field of work engagement studies which explains the relationship dynamics of how engaging leadership can make employees more engaged at work. The practical implications of this research can be in the form of company efforts to develop the ability of leaders to provide empowering, connecting, strengthening and inspiring support to their subordinates, to increase the work engagement of their subordinates.